Subcutaneous Fat Necrosis - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Subcutaneous fat necrosis (SCFN) is a rare dermatologic condition which until recently was thought to occur only in term neonates. Its presentations are protean and early in the disease; it mimics other more common neonatal dermatologic conditions. Although benign, it runs a prolonged course and may be associated with some complications and therefore needs to be differentiated from other more life-threatening neonatal dermatologic conditions. We present a case of a term neonate with histology report highlighting some characteristic features of SCFN and the need to differentiate it from sclerema neonatorum (SN), a condition associated with fatal outcome.